ผลของโปรแกรมการส่งเสริมพฤติกรรมสุขภาพต่อพฤติกรรมการปฏิบัติตัว เพื่อชะลอการเสื่อมของไตในผู้ป่วยโรคไตเรื้อรังระยะที่ 1-3a Effects of health behavioral promotion programs on behavior to slowing progression in patients with chronic kidney disease at 1 – 3a stage - แก่นของ, ขวัญเรือน; อนุตระกูลชัย, ศิริรัตน์; เลิศสินอุดม, สุณี; ธีรานุตร, อัมพรพรรณ (วารสารการพยาบาลและการดูแลสุขภาพ, 2019)
This quasi-experimental research, pretest-posttest control group design aimed to examine the effects of health behavioral promotion programs on behavior to slowing progression in patients with chronic kidney disease at 1 – 3a stage. Research samples were 76 patients with stage 1-3a of chronic kidney disease who received healthcare service at Nonmuang Health Promoting Hospital, Khon Kaen. The samples were divided into two equal groups, 38 patients in each group. The control group received a routine nursing care and the experimental group received health behavioral promotion programs based on Health Belief Model. The data had been collected for 3 months from April to June 2018. Research instruments consisted of : 1) the data collection instruments were 1.1) general information questionnaire 1.2) Health Belief Model assessment 1.3) questionnaire about behavior to slowing progression of chronic kidney disease ; and 2) experimental instruments were 2.1) Health behavioral promotion programs 2.2) behavior change manual to slowing progression of chronic kidney disease 2.3) video model of chronic kidney disease patient 2.4) flip charts about chronic kidney disease and behavior to slowing progression of chronic kidney disease 2.5) tool for increasing the perceived risk of end stage renal disease. Data were analyzed by using frequency, percentage, mean and standard deviation, median and min, max. Hypothesis was tested by Paired t-test, Independent t-test, Wilcoxon signed ranks test, Mann-Whitney U test and Chi-square test. The results of this research were 1) the experimental group got higher scores of Health Belief Model than the pretest and the control group statistical significance by .05; 2) the experimental group scored higher marks of behavior to slow progression of chronic kidney disease than the pretest and the control group statistical significance by .05